A REDEFINITION OF SELF: THE DESIGN, IMPLEMENTATION, AND IMPACT OF A CAREER EXPLORATION COURSE FOR STUDENTS ON ACADEMIC PROBATION - Bullington-Miller, Jordan (East Carolina University, 2022)
Students on academic probation are among the most vulnerable populations within higher education. Research indicates that following a semester of academic difficulty, students experience diminished self-efficacy and a decline in academic motivation. Evidence from a growing body of career development literature indicates that career exploration increases self-efficacy, improves decision-making, and enhances academic performance. Studies have explored the impacts of academic recovery programs and career development experiences as mutually exclusive interventions. No existing study previously explored the intersection of the two. This mixed methods case study assessed the impact of a career exploration course for students on academic probation. It examined the impact of the course on career self-efficacy and academic motivation, the value students assigned to such a course, and their experiences within it. The study explored the experiences of 15 students on or at risk of academic probation. Qualitative data suggested that career exploration contributed to increased confidence for students on probation. Quantitative data demonstrated statistically significant increases in the five competencies of career self-efficacy (occupational information, goal selection, planning, problem solving, and self-appraisal). Academic motivation declined in all three extrinsic motivation constructs and two intrinsic constructs (EM: external regulation, introjected, and identified; IM: toward accomplishment, and to know) with an increase in intrinsic motivation: to experience stimulation. However, the change in academic motivation was not statistically significant overall. Additional research is necessary to understand the predictive and mediating factors that contribute to the decline of academic motivation for students on academic probation.
Keywords: Academic probation; Career exploration; Career course; Academic motivation, Career self-efficacy; Academic recovery; Academic achievement; College attendance; Career development; Vocational guidance